Association Between Antipsychotic Treatment and Neurological Adverse Events in Pediatric Patients: A Population-Based Cohort Study in Korea - Jeon, Soo Min; Park, Susan; Kwon, Soonhak; Kwon, Jin-Won (Frontiers in Psychiatry, 2021)
Background: Potential adverse effects might be caused by increasing the number of antipsychotic prescriptions. However, the empirical evidence regarding pediatric psychiatric patients is insufficient. Therefore, we explored the antipsychotic-induced adverse effects focusing on the neurological system. Method: Using the medical information of pediatric patients retrieved from the claims data of Health Insurance Review and Assessment in Korea, we identified those psychiatric patients who were started on antipsychotic treatment at age 2–18 years between 2010 and 2018 (n = 10,969). In this study, movement disorders and seizures were considered as major neurological adverse events. The extended Cox model with time-varying covariates was applied to explore the association between antipsychotic medication and adverse events. Findings: Total 1,894 and 1,267 cases of movement disorders and seizures occurred in 32,046 and 33,280 person-years, respectively. The hazard risks of neurological adverse events were 3–8 times higher in the exposed to antipsychotics period than in the nonexposure period. Among the exposure periods, the most dangerous period was within 30 days of cumulative exposure. High doses or polypharmacy of antipsychotics was associated with increased risks of neurological adverse events. Among individual antipsychotics, haloperidol showed the highest risk of developing movement disorders among the examined agents. Quetiapine showed a lower risk of developing movement disorders but a higher risk of developing seizures than risperidone. Conclusion: These findings suggest that antipsychotics should be used with caution in pediatric patients, especially regarding initial exposure, high dose, and polypharmacy.